Positron emission tomography (PET) in cerebral amyloid angiopathy - Baron, Jean-Claude (Henry Stewart Talks, 2023)
Main challenges regarding CAA, Application of PET, Mapping Aβ amyloid in vivo with 11C-PiB, Sporadic probable CAA compared to AD, PiB uptake across the whole cerebral cortex, Global cortical amyloid uptake positivity (sensitivity), Regional amyloid uptake in CAA vs. AD (specificity), FDG PET may differentiate CAA from AD, PET tracers with greater specificity for Aβ40